MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYAH MELALUI PERMAINAN KARTU HURUF PADA ANAK USIA DINI KELOMPOK B di TK MUSLIMAT NU NURUL ISLAM 4 - Ermawati; Harliana; Amir (Jurnal Eduakasi dan Penelitian Tindakan Kelas, 2023)
Early age is often referred to as the golden age (Golden Age) during which all aspects of development in children experience very significant development and this is the right time for parents and teachers to lay the foundations of the skills they will develop. To introduce letters hijaiyah to children after early childhood in some PAUD institutions are still applying conventional methods by using the book Iqro '. Introduction of hijaiyah letters can be varied by using hijaiyah letter cards. Learning model in the conventional way. This study wants to see the effectiveness of the use of hijaiyah letters in improving the ability to read hijaiyah letters in early childhood in PAUD. The research method used in this study is Classroom Action Research (CAR). The results showed that the ability to read hijaiyah letters in B2 class PAUD Arrahma Siak Hulu increased by using hijaiyah letter media development. Evidenced by the results of cycle 1 that 50% complete reading hijaiyah letters while in increased to 93.75%